Applied mechatronics and mechanics : system integration and design - Singh, Satya Bir; Ranjan, Prabhat; Haghi, A. K. (canada apple academic press inc., 2021)
"This research-oriented book, Applied Mechatronics and Mechanics: System Integration and Design, presents a clear and comprehensive introduction to applied mechatronics and mechanics. It presents some of the latest research and technical notes in the field of mechatronics and focuses on the application considerations and relevant practical issues that arise in the selection and design of mechatronics components and systems as well. In the field of mechatronics and mechanics, the variety of materials and their properties is reflected by the concepts and techniques needed to understand them: a rich mixture of mathematics, physics, and experiment. These are all combined in this informative book, based on the chapter authors' years of experience in research and teaching. With the inclusion of several case studies, this valuable volume will enable readers to comprehend and design mechatronic systems by providing a frame of understanding to develop a truly interdisciplinary and integrated approach to engineering. It will be helpful to faculty and advanced students as well as specialists from all pertinent disciplines"--
Keywords: Mechatronics; Mechanics, Applied